2013
DOI: 10.1186/1471-2164-14-406
|View full text |Cite
|
Sign up to set email alerts
|

Combined methylation mapping of 5mC and 5hmC during early embryonic stages in bovine

Abstract: BackgroundIt was recently established that changes in methylation during development are dynamic and involve both methylation and demethylation processes. Yet, which genomic sites are changing and what are the contributions of methylation (5mC) and hydroxymethylation (5hmC) to this epigenetic remodeling is still unknown. When studying early development, options for methylation profiling are limited by the unavailability of sufficient DNA material from these scarce samples and limitations are aggravated in non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 82 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…4 a, b, 24 h post-IVF the pPN in control zygotes shows a dramatically reduced 5mC signal compared with the mPN, which still retained DNA methylation. These results are consistent with previous reports, showing that also the paternal genome in bovine embryos undergoes DNA demethylation [ 17 , 42 , 78 ]. Remarkably, zygotes fertilized with sperm treated with H 2 O 2 retained higher levels of DNA methylation, indicating that the active DNA demethylation process in the pPN is compromised (Fig.…”
Section: Resultssupporting
confidence: 94%
“…4 a, b, 24 h post-IVF the pPN in control zygotes shows a dramatically reduced 5mC signal compared with the mPN, which still retained DNA methylation. These results are consistent with previous reports, showing that also the paternal genome in bovine embryos undergoes DNA demethylation [ 17 , 42 , 78 ]. Remarkably, zygotes fertilized with sperm treated with H 2 O 2 retained higher levels of DNA methylation, indicating that the active DNA demethylation process in the pPN is compromised (Fig.…”
Section: Resultssupporting
confidence: 94%
“…These areas that are below the resolution of conventional confocal microscopy (~100 nm axial and up to ~500 nm vertical) may present captured 5mC-rich sites that were possibly undergoing active DNA demethylation through oxidation and conversion to 5hmC. Several lines of evidence exist that describe DNA methylation and demethylation as dynamic processes, with hypomethylation occurring during the embryonic blastocyst stage and also lasting through differentiation [41,42]. Previously we had observed that up to the sixth day in early differentiation the mouse genome becomes predominantly hypermethylated, first in its euchromatic compartments followed by heterochromatin [7].…”
Section: Discussionmentioning
confidence: 99%
“…The microarray DNA probes included at least one CpG and were designed based on a methylation-specific deep sequencing analysis of the bovine genome that generated 1.2 million reads from genomic libraries from Day 7 blastocysts and Day 12 elongated embryos [52]. The microarray contained 414 566 probes surveying 20 355 genes as well as 34 379 CpG islands.…”
Section: Analysis Of Methylomementioning
confidence: 99%